Cemaran Mikroba Berdasarkan Angka Lempeng Total dan Angka Paling Mungkin Koliform pada Minuman Air Tebu (Saccharum officinarum) di Kota Pontianak - Riza Linda, Muhammad Miki Fauzi, Rahmawati, (Universitas Tanjungpura, 2017)
Sugarcane juice is a drink that is quite favored by the people in Pontianak city. However, most sellers of sugarcane juice do not pay attention to hygiene in the use of equipment, storage and processing of sugarcane juice. This can be a cause of microbial contamination in sugarcane juice. The research aims to determine the microbial contamination based on the examination of Total Plate Count (TPC) and Most Probable Number (MPN) coliform in sugarcane (Saccharum officinarum) juice in Pontianak city. The samples in this research were sugarcane juice drinks without ice taken each 10% of the total sellers randomly in every district in the city of Pontianak. This is a descriptive study using TPC and MPN coliform methods, and supporting data such as temperature, humidity and hygiene factor. The results of the 30 samples tested showed the average TPC ranging from 2,4 x 104 to 1,7 x 105 CFU/ml and the avarage value of MPN coliform was >1100 CFU /ml. The values exceeding the threshold value of microbial contamination in juice drinks based on SNI 3719: 2014 in which for TPC the maximum is 1 x 104 CFU/ml, and for MPN coliform the maximum is 20 CFU/ml